2006
DOI: 10.1152/ajpregu.00793.2005
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation and remote organ damage following bilateral femur fracture requires Toll-like receptor 4

Abstract: Extensive soft tissue injury and bone fracture are significant contributors to the initial systemic inflammatory response in multiply injured patients. Systemic inflammation can lead to organ dysfunction remote from the site of traumatic injury. The mechanisms underlying the recognition of peripheral injury and the subsequent activation of the immune response are unknown. Toll-like receptors (TLRs) recognize microbial products but also may recognize danger signals released from damaged tissues. Here we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 66 publications
(74 reference statements)
7
81
0
Order By: Relevance
“…Avoiding undesirable manipulation forces, while obtaining an acceptable alignment, is important to prevent additional injury to soft tissues. [14] In this study, we describe the design and preliminary clinical evaluation of an automated system developed to provide detailed information about the three-dimensional forces and moments applied by a surgeon during the Figure 6. Changes in the traction force measured over the entire fracture reduction procedure.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Avoiding undesirable manipulation forces, while obtaining an acceptable alignment, is important to prevent additional injury to soft tissues. [14] In this study, we describe the design and preliminary clinical evaluation of an automated system developed to provide detailed information about the three-dimensional forces and moments applied by a surgeon during the Figure 6. Changes in the traction force measured over the entire fracture reduction procedure.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…We measured NF-jB activity using electrophoretic mobility shift assays with nuclear extracts prepared from the tissue. Electrophoretic mobility shift assays were performed as described previously [21].…”
Section: Methodsmentioning
confidence: 99%
“…Studies of cytokine pattern and the evolution of remote organ dysfunction after bilateral femur fractures in mice [13,18,21] demonstrate such trauma initiates a complex systemic inflammatory response in which the pro-and antiinflammatory cytokines, such as IL-6 and IL-10, play a pivotal role in systemic inflammation [18,21]. Kobbe et al [19] demonstrated fracture-associated soft tissue injury is a major contributor to the systemic inflammation found after long-bone fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanics of the activation pathway therefore remain unclear. A variety of receptor interactions have been identified in vitro 33,36,45,76 . In animal trauma models, a Toll-like receptor (TLR) 4 mechanism has been convincingly established for HMGB1 37 .…”
Section: Alarmins Released Passively By Damageinduced (Non-programmedmentioning
confidence: 99%